Rotational malalignment in femoral nailing: prevention, diagnosis and surgical correction - Branca Vergano, Luigi; Coviello, Gianluca; Monesi, Mauro (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: to review and discuss the literature about rotational malalignment during and after femoral nailing.Methods: analysis of the literature on prevention and evaluation of rotation during femoral nailing, clinical and subjective consequences of malrotation and techniques used to correct the deformity, both in the acute and chronic phase.Results: malrotation is very common after femoral nailing. The exact definition of a malrotated femur is controversial, but it is widely agreed that a rotational malalignment 30° is a deformity which requires correction. The complaints of the patients with a malrotated femur can be various and can involve the hip, the knee or below the knee. The ability to compensate for the deformity while standing and walking may decrease the symptoms. Surgical correction is feasible with many techniques and devices: the procedure involving derotation, changing the locking screws and maintaining the nail is safe, reproducible and relatively easy.Conclusions: prevention of malrotation during femoral nailing is the cornerstone of successful operation outcomes. If rotational malalignment is suspected, prompt diagnosis and adequate surgical treatment are mandatory to overcome this common complication.